Kepemimpinan Kh. Hasyim Asy’ari, Kh. Abdul Wahab Hasbullah Dan Kh. Bisri Syansuri Dalam Membentuk Karakteristik Kepemimpinan Santri Di Pondok Pesantren Di Jombang - Hidayah, Bashirotul (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Kyai leadership is something that has a major influence on the development of the santri, especially the formation of the character of the santri, not the case in terms of leadership. This study aims to determine the leadership pattern of KH. Hasyim Asy'ari, KH. Abdul Wahab Hasbullah and KH. Bisri Syansuri in shaping the characteristics of the leadership of students at Islamic boarding schools in Jombang and the formation of the character of the leadership of students by KH. Hasyim Asy'ari, KH. Abdul Wahab Hasbullah and KH. Bisri Syansuri at a boarding school in Jombang. The method used in this study is a library research method in which data sources are obtained from books, journals, scientific papers, magazines, and others. For supporting sources, interviews were also conducted with the Kyai dzurriyah. After obtaining the data needed by the author, the data is described and then analyzed. The results of the study prove that the role of the kiai is very influential in the leadership spirit of the santri. KH's leadership style. Hasyim Asy'ari is a transformational leadership style, KH. Abdul Wahab Hasbullah applied his democratic leadership style, while KH. Bisri Syansuri is a kyai who has a firm and flexible attitude. Kiai places himself as a leader, manager, entertainer, entrepreneur, father, teacher, servicer, and designer for students.